Diffusive clustering in an infinite system of hierarchically interacting diffusions - Fleischmann, Klaus; Greven, Andreas (Probability Theory and Related Fields, 1994)
We study a countable system of interacting diffusions on the interval [0,1], indexed by a hierarchical group. A particular choice of the interaction guaranties, we are in the diffusive clustering regime. This means clusters of components with values either close to 0 or close to 1 grow on various different scales. However, single components oscillate infinitely often between values close to 0 and close to 1 in such a way that they spend fraction one of their time together and close to the boundary. The processes in the whole class considered and starting with a shift-ergodic initial law have the same qualitative properties (universality). © 1994 Springer-Verla